Equations of Motion of a Rigid Body with Two Elastic Rods - D. A. Eliseev; E. P. Kubyshkin (Моделирование и анализ информационных систем, 2014)
In the paper we propose a mathematical model of a mechanical system consisting of a rigid body and two rigidly connected elastic straight rods located in the same plane. The system rotates around the axis passing through the mass center of a rigid body and perpendicular to the plane of the rods. The rods are modeled by the Euler–Bernoulli beam. The mathematical model is an initial-boundary value problem for a hybrid system of differential equations. The cases of fast and slow rotations of the system are considered.